Prediction of hydrocarbon source rock distribution using logging curves: A case study of Es32 source rock in Nanpu Sag, Huanghua depression, Bohai Bay Basin - Guo, Qianwen; Jiang, Shan; Wang, Jianwei; Zhou, Quanzhen; Gao, Yongliang; Ye, Lin; Yin, Jie (Frontiers in Earth Science, 2023)
The Es3 is the main hydrocarbon source rock system in the Nanpu Sag. Finally, the TOC and hydrocarbon potential of each sub depression of Es3were predicted. The study shows that the hydrocarbon source rocks of Es32 and Es34 sections are mainly of type II2 and type II1 respectively, with good organic matter type and high maturity. Biomarker compound parameters indicate that the Es32 section hydrocarbon source rocks developed in a semi-saline, low to medium terrestrial source organic matter supplied reduction environment with a high algal contribution; the Es34 section hydrocarbon source rocks formed in a freshwater, low terrestrial source supplied reduction environment with a medium-high algal contribution. The multiple linear regression method is more effective than the ΔlgR method in predicting hydrocarbon source rocks in the Nanpu Sag, and the prediction accuracy is higher; the correlation between TOC and S1+S2 is the best in the model for predicting hydrocarbon potential. The TOC and hydrocarbon potential of the hydrocarbon source rocks in Es31 are generally low; the high value area of TOC and hydrocarbon potential of the hydrocarbon source rocks in Es32 is partly between the No.1 tectonic zone and No.5 tectonic zone in Linque sub depression, and the TOC and hydrocarbon potential of the hydrocarbon source rocks in Liunan sub depression are larger; the high value area of TOC and hydrocarbon potential of the hydrocarbon source rocks in Es34 is mainly concentrated in Shichang sub depression.